Formation of nanosized zirconia-supported 12-tungstophosphoric acid in mesoporous silica SBA-15: a stable and versatile solid acid catalyst for benzylation of phenol - Sawant, D. P.; Vinu, A.; Jacob, Nalini E.; Lefebvre, F.; Halligudi, Shivappa B. (Journal of Catalysis, 2005)
A nanosized zirconia-supported 12-tungstophosphoric acid (TPA) in SBA-15 composite was prepared by wet impregnation of TPA/ZrO2 nanoparticles inside the mesoporous channels of SBA-15. The resulting composite material was calcined at 1123 K and characterized by elemental analysis, powder X-ray diffraction, nitrogen adsorption isotherms, transmission electron microscopy (TEM), scanning electron microscopy (SEM), solid-state P-31 CP-MAS NMR, Si-29 MAS NMR, UV-vis diffuse reflectance spectra, FTIR, TPD of ammonia, FTIR pyridine adsorption, and thermogravimetric analysis (TG-DTG). The synthesized TPA/ZrO2/SBA-15 showed a well-ordered hexagonal inesoporous structure and mesoporous support SBA-15 stabilized ZrO2-t (tetragonal) phase with crystal size in the range of 3-4 nm. SBA-15 was a better support than MCM-41 and MCM-48 because it retained its mesostructure even after high TPA loading and high calcination temperatures. Mesoporous silica support plays an important role in stabilizing the catalytically active tetragonal phase of zirconia, which gave the most active catalysts. The catalysts were examined for their catalytic activities in the liquid phase benzylation of phenol with benzyl alcohol and the catalyst 15 wt% TPA/ 22.4 wt% ZrO2/SBA-15 calcined at 1123 K was found to have high acidity and to be 10 times more active than neat TPA/ZrO2 Under the reaction conditions studied in benzylation of phenol. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: nanosized; phenol benzylation reaction; terragonal phase; TPA/ZrO2